Нью-Йорк - Москва - Любовь: [роман] / Анна Берсенева - Берсенева Анна (My Best, 2006)
Экземпляры: ф.8 (2008) / Инвентарный номер: 52367 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44^VLBC/RL